A pair of DICER1‐positive monozygotic twins: One with pleuropulmonary blastoma, another with acute transient hepatitis. Issue 12 (8th July 2017) - Li, Sihui; Cai, Siyu; Wang, Xisi; Zhang, Dawei; Fu, Libing; Zeng, Qi; Peng, Xiaoxia; Ma, Xiaoli
Abstract: Pleuropulmonary blastoma (PPB) is the most common primary malignant neoplasm of the lung in children that is associated with a germline mutation in DICER1 . In this report, we share an interesting case of a pair of monozygotic twins: one of them developed PPB when she was 4‐year old, while the other developed acute transient hepatitis when she was 5‐year old. Next‐Gen sequencing for DICER1 mutations of their family revealed that both twins and their mother had c.C3675A mutation. The mother also had a history of multinodular goiter. Identification of DICER1 mutation carriers and close surveillance of individuals at risk for DICER1 syndrome may allow early detection and hence better outcome.